O-ZONE: affordable stratospheric air dynamic sampling device - Federico Toson; Matilde Pavan; Dumitrita Sandu; Simone Sandon; Marco Furiato; Luigi Antoniazzi; Giovanni Righi; Antonino Pitarresi; Mauro Pulice; David Magnani; Daniele Panariti; Andrea Conte; et al. (2022)
The current situation regarding air pollution, global warming and the world approaching the point of no return have led the United Nations to focus on improving the environmental situation through the SDGs [1]. In line with these ambitions, O-ZONE team, was born in 2019 with the clear objective of taking concrete action against climate change [2]. The team's goal is to build a compact, low-cost, and reusable device to sample stratospheric pollutants, at various altitudes and thus provide air quality indications in mid-range areas for monitoring, prevention, and rapid intervention in case of unpredictable events. The O-ZONE team was therefore born as an idea of some students from the Aerospace Engineering course at the same University. The students took part in the REXUS/BEXUS project by Swedish National Space Agency (SNSA), Deutsches Zentrum für Luft- und Raumfahrt (DLR) and European Space Agency (ESA) [3]. As in each of these projects, the team tackled the various steps of space missions but, in this case, with extra constraints. They had to work during the lockdown with various complications due to the pandemic. Although the launch was delayed, the students carried on with their motivation and then launched their device on board the BEXUS 30. The prototype launched in Kiruna - Sweden (at the Esrange base), and which reached an altitude of 27.8 km, is a sampling system for Volatile Organic Compounds (VOCs), such as NOX and SOX, Particulate Matter (PM) and Chlorofluorocarbons (CFCs) responsible for the depletion of the Ozone layer [4]. These types of samplers [2] fill the technological gap in atmospheric analysis; the current state of the art allows air to be monitored only statically from ground stations or by satellite analysis [5], while O-ZONE presents an accessible, easy-to-use and rapid in situ sampling method. This paper describes the technical specifications and design aspects of the device and the experience that has allowed the students to grow as a team, especially in terms of personal skills and the ...